1997
DOI: 10.1111/j.1399-6576.1997.tb04863.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation and vasodilator responses by isoflurane and desflurane in the feline renal vascular bed

Abstract: The renal autoregulatory capacity was not attenuated by either ISO or DES. These agents produced equipotent renal vasodilation, which was not more powerful than that produced by autoregulation alone. The renal vasorelaxant effects of ISO and DES may therefore to a substantial extent be attributable to autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Once the mean arterial pressure declined beyond this break-point, significant reductions in portal blood flow occurred. By extrapolating data from other vascular beds, it does not seem likely that DES impairs the autoregulatory capacity in settings above this perfusion pressure (9). We therefore suggest that the observations in the present study can be explained by effective autoregulatory vasodilation at pressures above 70 mm Hg within the splanchnic region and, in particular, within the intestine.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Once the mean arterial pressure declined beyond this break-point, significant reductions in portal blood flow occurred. By extrapolating data from other vascular beds, it does not seem likely that DES impairs the autoregulatory capacity in settings above this perfusion pressure (9). We therefore suggest that the observations in the present study can be explained by effective autoregulatory vasodilation at pressures above 70 mm Hg within the splanchnic region and, in particular, within the intestine.…”
Section: Discussionsupporting
confidence: 53%
“…Local vascular relaxation is expected (5), while decreases in perfusion pressure are likely to be produced by the negative inotropic cardiac effects of DES (6,8). In addition, effects mediated through autoregulation (9), baroreflex alterations and central nervous inhibition of sympathetic neurogenic vasoconstrictor discharge can concur. In the present study, all these mechanisms were unrestricted and allowed to have free play.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that isoflurane and desflurane can cause renal vasodilation in cats (38). Gas anesthetic-induced vasodilation has also been found in other tissues such as the mesenteric and coronary circulation (11,21).…”
Section: Discussionmentioning
confidence: 98%
“…45,47 In cats, administration of desflurane and isoflurane within usual ranges of anesthetic concentrations did not alter the autoregulation of renal blood flow at perfusion pressures >90 mm Hg. 48 In dogs, desflurane and isoflurane did not alter the pattern of myocardial blood flow distribution. 44,49 In pigs, sevoflurane decreased myocardial perfusion by an amount consistent with the associated decrease in myocardial work.…”
Section: Microcirculatory and Tissue Perfusion Changes During Anesthementioning
confidence: 98%